The effect of swimming in meltdown reaction among children with autism / Maisarah Mohd Saleh … [et al.] - Mohd Saleh, Maisarah; Abd Hamid, Siti Fadhillah; Abd Razak, Fatin Aqilah; Sabadri, Saidatul Nur Syuhadah; Mohd Rafi, Nur Natasya Nadeeya (Faculty of Sport Science and Recreation, Universiti Teknologi MARA, 2019)
This study conducted to identify the effect of swimming in reducing meltdown in children with autism in Pusat Akuatik Darul Ehsan. The study focused on effect of before and after swimming towards children with autism at Pusat Akuatik Darul Ehsan. There were 25 children with autism aged between 4 to 7 years old were involved. The instrument used in this study was The Multidimensional Assessment of Preschool Disruptive Behavior (MAP-DB) questionnaire. The parents with autism kids were asked to answer the questionnaires before swimming class and after 2 months of swimming classes to evaluate their children. Paired t-test was used to identify the differences effect between before swimming and after swimming. The result showed that all the components of the MAP-DB questionnaire have significant effects in reducing meltdown towards autism (p=0.000). In a nutshell, this study implied that that swimming had significant effect for autism kids in reducing meltdown.